Distribution of Temperature and Salinity on Fishing Zone in The Regional Fisheries Management of Indonesia (WPP-RI) 573 - Wahyudi, Andri; Ginanjar, Martin Anjar; Alfaris, Lulut (Indo-MathEdu Intellectuals Journal, 2025)
The Fisheries Management Republik Indonesia (WPP-RI) 573 encompasses strategic waters in the southern Indian Ocean of Indonesia, playing a critical role in global ocean circulation through the Indonesian Throughflow (ITF). This study aims to examine the physical oceanographic characteristics, particularly sea surface temperature (SST), salinity, and marine ecosystem productivity in WPP 573, as well as the impacts of ITF variability on these parameters. Data utilized include SST, salinity, and current velocity obtained from satellite observations and numerical models. The analysis reveals that the ITF transports tropical water masses from the Pacific Ocean to the Indian Ocean, significantly influencing the spatial and temporal distribution of temperature and salinity in the region.